Bombardment of Vienna on the night of the 11th to the 12th of May [1809] - Piringer, Benedikt, 1780-1826 (engraver):::Creator::::::::::::; Hoechle, Johann Nepomuk, 1790-1835, artist:::Contributor:::::::::::: (France; L'imprimerie de Langlois; Paris)
Color illustration of the siege of Vienna on May 11-12, 1809